Metabolismo e crescimento de Ricinus Communis L. sob temperatura supraótima e elevado nível de CO2. - Silva, Fabíola Vanessa de França (2011)
Castor bean (Ricinus communis L. - Euphorbiaceae) is an oilseed metabolism of C3, rustic, resistant to drought, probably originated in Ethiopia, cultivated in a wide latitude because it has good adaptative capacity. The commercial application of culture is broad in agriculture and industry, being the oil and intake its main products. Given the environmental changes underway, aggravated by increased consumption of fossil fuels, many biochemical and physiological impacts may affect the productivity of important crops, such as castor bean. So, the main goal of this project was to evaluate biochemical and physiological impacts on castor bean in response to high temperature and increased CO2. The experiment was conducted in Phytotron located at Embrapa Algodão, in 2010. We adopted a experiment completely randomized experimental design with four treatments in a factorial combination of two temperatures (30 and 37ºC) and two levels of CO2 (400 and 800 ppm), with four replicates, obtained in five surveys over the cycle, comprising 80 sample units. The growth analysis proceeded as well as the quantification of photosynthetic rate, transpiration, stomatal conductance, electrolyte leakage, accumulation of solutes in symplasm, photosynthetic pigments and soluble carbohydrates. The increase concentration of atmospheric CO2 and temperature elevation benefited to cultivate in the early stages of growth, however, as the phenological cycle progressed both factors, independently of the majority of variables, they acted negatively on the biochemistry and physiology of the castor bean, which showed a reduction in growth rate, decrease in net photosynthesis, transpiration, stomatal conductance and levels of chlorophyll a, b, and total; accumulation of solutes in simplasma, reducing the osmotic potential, and soluble carbohydrates in the roots.